The Influence of Regional Specialization in Agriculture on Farmers’ Pest Control Behaviors Based on a Dual Examination of Control Strategies and Control Costs - Xin Tan; Guanghua Lin (Agriculture)
The pest control behaviors of agricultural producers are crucial not only for effectively managing pests and diseases but also for ensuring the sustainable development of agricultural production and the environment. Regional specialization in agriculture, as a typical method to optimize planting structure, influences farmers’ control behaviors through dual mechanisms. However, existing research has largely overlooked this issue. This paper systematically examines the influence and mechanisms of agricultural regional specialization on farmers’ pest control strategies and costs. Using village tracking research data and farmer data from the Jiangsu, Sichuan, and Jilin provinces of China over 15 years, the study employs fixed-effects models and the instrumental variable method to provide empirical evidence. The research results indicate that by reducing biological diversity, which exacerbates the occurrence and damage of pests and diseases, and increasing the homogeneity of planting structures, the development of regional specialization in agriculture prompts farmers to shift their control strategy from “ex post treatment” to “ex ante prevention” and has increased the control costs. The policy implication is that farmers should be encouraged to practice moderate crop rotation in rapidly increasing regional specialization. Additionally, strengthening real-time monitoring of pest and disease dynamics is essential to guide farmers in early prevention and timely control.